Case Report: Clinical Responses to Tislelizumab as a First-Line Therapy for Primary Hepatocellular Carcinoma With B-Cell Indolent Lymphoma - Li, Qijun; Dong, Yong; Pan, Yubin; Tang, Honglin; Li, Da (Frontiers in Immunology, 2021)
Background: As an emerging therapy with a promising efficacy, immunotherapy has been widely used in the treatment of solid tumors and hematologic malignancies. This clinical study compares the efficacy of tislelizumab, a domestic immune checkpoint inhibitor (ICI), to that of sorafenib when used as a first-line therapeutic option in hepatocellular carcinoma (HCC). And the concurrence of HCC and non-Hodgkin's lymphoma (NHL) is rare, especially in the treatment of ICIs. Case presentation: A 61-year-old patient presenting with primary HCC and indolent B-cell lymphoma, had a partial clinical response to tislelizumab for his primary HCC. Besides, we described a phenomenon of pseudo-progression and delayed diagnosis of his lymphoma during long course of treatment. Conclusion: Tislelizumab, an immunotherapeutic option with a favorable efficacy and toxicity, can be used to manage double primary tumors. However, studies should aim at elucidating the probable mechanisms of this therapy. Pseudo-progression and separation remission make treatment of double primary tumors even more challenging, which calls for additional caution in patients undergoing immunotherapy to avoid misdiagnosis and, therefore, begin early appropriate interventions.